2020
DOI: 10.1017/s1431927620024861
|View full text |Cite
|
Sign up to set email alerts
|

Structural Relationships Between Interstitial Cells of Cajal and Smooth Muscle Cells/Nerve Fibers in the Gastric Muscularis Mucosae of Chinese Giant Salamander

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…It induces the pacemaker activity of ICC, and then ICC generate and transmit electrical slow wave to the SMC to regulate the contraction and relaxation of SMC. Therefore, ICC serve mediators of enteric motor neurotransmission, and they were involved in neuromuscular signaling transmission since ICC and SMC establish direct contact between them (Lino & Horiguchi, 2006; Yu et al, 2020). Additionally, in the present study, the multivesicular bodies, including exosomes, were observed in close proximity to ICC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It induces the pacemaker activity of ICC, and then ICC generate and transmit electrical slow wave to the SMC to regulate the contraction and relaxation of SMC. Therefore, ICC serve mediators of enteric motor neurotransmission, and they were involved in neuromuscular signaling transmission since ICC and SMC establish direct contact between them (Lino & Horiguchi, 2006; Yu et al, 2020). Additionally, in the present study, the multivesicular bodies, including exosomes, were observed in close proximity to ICC.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional paraffin sectioning technique was employed to observe the microstructure of the gastric wall of the R. catesbeiana (Yu et al, 2020). The gastric wall samples were removed from the fixative and were washed with water.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations